2011
DOI: 10.1002/jclp.20836
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor and measurement invariance analyses of the emotion regulation questionnaire

Abstract: Emotion regulation is widely studied in many areas of psychology and the number of publications on emotion regulation has increased exponentially over the past few decades. Additionally, interest in the relationships between emotion dysregulation processes and psychopathology has drastically increased in recent years. The Emotion Regulation Questionnaire (ERQ) was developed to measure two specific constructs related to emotion control: reappraisal and suppression (Gross & John, 2003). In its initial validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
83
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 60 publications
13
83
3
3
Order By: Relevance
“…The orthogonal/ independent model showed to be the best fit among different models tested, confirming that reappraisal and suppression are two independent emotion regulatory strategies that adolescents use differently across daily contexts and situations. This result is consistent (Balzarotti et al 2010;Cabello et al 2013;Gross and John 2003;Gullone and Taffe 2012;John and Gross 2004;Melka et al 2011). This Portuguese questionnaire (QRE-CA) revealed an acceptable internal consistency for the reappraisal subscale.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The orthogonal/ independent model showed to be the best fit among different models tested, confirming that reappraisal and suppression are two independent emotion regulatory strategies that adolescents use differently across daily contexts and situations. This result is consistent (Balzarotti et al 2010;Cabello et al 2013;Gross and John 2003;Gullone and Taffe 2012;John and Gross 2004;Melka et al 2011). This Portuguese questionnaire (QRE-CA) revealed an acceptable internal consistency for the reappraisal subscale.…”
Section: Discussionsupporting
confidence: 89%
“…Also, the decision between models should rely on previous research (Preacher 2006). Studies with the ERQ-CA have shown that reappraisal and suppression subscales are orthogonal, meaning that these are two independent emotion regulatory strategies (Balzarotti et al 2010;Cabello et al 2013;Gross and John 2003;Gullone and Taffe 2012;John and Gross 2004;Melka et al 2011). Hence, for these two reasons we chose model C (Fig.…”
Section: Construct Validitymentioning
confidence: 98%
“…Testiranjem polnih razlika dobijeno je da muškarci ostvaruju više skorove na ES, dok razlike u KP nisu značajne, što je u skladu sa ranijim istraživanjima (Balzarotti et al, 2010;Cabello et al, 2013;Gross & John, 2003;Melka et al, 2011;Wiltink et al, 2011). Ipak, veličina Cohenovog d koeficijenta ukazuje na to da su razlike male (Cohen, 1988), tako da će se dalja analiza raditi na celom uzorku.…”
Section: Rezultatiunclassified
“…Naime, u primeni na studentskoj populaciji dosledno se dobijaju polne razlike u emocionalnoj supresiji, pri čemu muškarci ostvaruju više skorove, dok u kognitivnoj preformulaciji nisu zabeležene polne razlike (Gross & John, 2003;John & Gross, 2004;Melka et al, 2011). Međutim, istraživanja na opštoj populaciji ne daju tako jednoznačne rezultate.…”
unclassified
“…Furthermore, the two regulation styles have been found to be significantly associated with parents' usage of supportive and nonsupportive contingent reactions (Meyer et al, 2014). The measure has demonstrated good internal reliability, test-retest reliability, and measurement equivalence across gender and ethnicity (Gross & John, 2003;Melka, Lancaster, Bryant, & Rodriguez, 2011). Within the current study, …”
Section: Parent Emotion Regulationmentioning
confidence: 76%